The Effect of Canva-Based Interactive Learning Media Implementation On The Interest In Learning Sciences of Grade V at SDIT Plus Qurthuba - Auliaa Amanda Fahmi; Andi Halimah; Immawati Nur Aisyah Rivai (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The research discusses: 1) How is the interest in learning science in fifth grade in the experimental group from the implementation of Canva-based interactive learning media, 2) How is the interest in learning science in fifth grade in the control group without the implementation of Canva-based interactive learning media, 3) Is there an influence of Canva-based interactive learning media on the interest in learning science in fifth grade in SDIT Plus Qurthuba. The type of research used is quantitative with a quasi-experimental method using a Pretest-Posttest non-equivalent control group design. The data analysis technique used is descriptive statistical analysis and the Mann-Whitney hypothesis test. The results show that the interest in learning science in fifth grade students in the experimental group from the implementation of Canva-based interactive learning media has a higher average value compared to fifth grade in the control group without the implementation of Canva-based interactive learning media. The results of the differences can also be seen from the difference in the increase in the mean rank in the experimental group from the implementation of Canva-based interactive learning media which is higher than the control group without the implementation of Canva-based interactive learning media.